Different Expression of Duodenal Genes Related to Insulin Resistance Between Nonobese Women and Those with Severe Obesity - Ho-Plagaro, Ailec; Santiago-Fernandez, Concepción; Rodríguez-Díaz, Cristina; Lopez-Gómez, Carlos; Garcia-Serrano, Sara; Rodríguez-Pacheco, Francisca; Valdes, Sergio; Rodríguez-Cañete, Alberto; Alcaín-Martínez, Guillermo; Ruiz-Santana, Natalia; Vázquez-Pedreño, Luis; García-Fuentes, Eduardo (Obesity (Silver Spring, Md.), 2020)
The study aim was to identify changes in duodenal gene expression associated with the development of insulin resistance according to the BMI of women. Duodenal samples were assessed by microarray in four groups of women, nonobese women and women with severe obesity, with both low and high insulin resistance. There was a group of shared downregulated differentially expressed genes (DEGs) related to tissue homeostasis and antimicrobial humoral response in women with higher insulin resistance both with severe obesity and without obesity. In the exclusive DEGs found in severe obesity, downregulated DEGs related to the regulation of the defense response to bacterium and cell adhesion, involving pathways related to the immune system, inflammation, and xenobiotic metabolism, were observed. In the exclusive DEGs from nonobese women with higher insulin resistance, upregulated DEGs mainly related to the regulation of lipoprotein lipase activity, very low-density lipoprotein particle remodeling, lipid metabolic process, antigen processing, and the presentation of peptide antigen were found. Independent of BMI, higher insulin resistance was associated with a downregulation of duodenal DEGs mainly related to the immune system, inflammation, and xenobiotic metabolism. Also, intestinal lipoprotein metabolism may have a certain relevance in the regulation of insulin resistance in nonobese women.